Proceedings of the 31st ACM SIGMOD-SIGACT-SIGAI Symposium on Principles of Database Systems 2012
DOI: 10.1145/2213556.2213566
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic regular expressions in linear time

Abstract: Deterministic regular expressions are widely used in XML processing. For instance, all regular expressions in DTDs and XML Schemas are required to be deterministic. In this paper we show that determinism of a regular expression e can be tested in linear time. The best known algorithms, based on the Glushkov automaton, require O(σ|e|) time, where σ is the number of distinct symbols in e. We further show that matching a word w against an expression e can be achieved in combined linear time O(|e| + |w|), for a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Checking all possible configurations of a loop for every loop used in a regular expression for the language is intractable. We could use a standardized configuration of a loop, such as the unambiguous form from [5]. For a regular expression composed of regular expressions x, y, define x(yx) * to be the unambiguous form, as a DFA is easily constructed from it.…”
Section: Adapting Minlang For Infinite Languagesmentioning
confidence: 99%
“…Checking all possible configurations of a loop for every loop used in a regular expression for the language is intractable. We could use a standardized configuration of a loop, such as the unambiguous form from [5]. For a regular expression composed of regular expressions x, y, define x(yx) * to be the unambiguous form, as a DFA is easily constructed from it.…”
Section: Adapting Minlang For Infinite Languagesmentioning
confidence: 99%
“…Checking all possible configurations of a loop for every loop used in a regular expression for the language is intractable. We could use a standardized configuration of a loop, such as the unambiguous form from [14]. For a regular expression composed of regular expressions x, y, define x(yx) * to be the unambiguous form, as a DFA is easily constructed from it.…”
Section: Adapting M Inlang For Infinite Languagesmentioning
confidence: 99%
“…Since then, DREs have been studied in the context of language approximations [15], learning [16], descriptional complexity [17,18] and static analysis [19,20]. Recently, it was shown that testing if a regular expression is deterministic can be done in linear time [21].…”
Section: Introductionmentioning
confidence: 99%